2013
DOI: 10.1152/ajplung.00411.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced microtubule acetylation in cystic fibrosis epithelial cells

Abstract: Dysfunctional cystic fibrosis transmembrane conductance regulator (CFTR) leads to many cellular consequences, including perinuclear accumulation of free cholesterol due to impaired endosomal transport. The hypothesis being tested is that CF-related perinuclear cholesterol accumulation due to disrupted endocytic trafficking occurs as a result of reduced microtubule (MT) acetylation. Here, it is identified that acetylated-α-tubulin (Ac-tub) content is reduced by ∼40% compared with respective wild-type controls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 39 publications
(49 reference statements)
9
83
0
Order By: Relevance
“…To test this hypothesis, expression of TPPP was reduced in immortalized human tracheal 9/HTEo 2 cells. We have previously published that microtubules in CF cell tissues exhibit reduced acetylation compared with controls (16). In this article, we present data showing reduced rates of microtubule formation.…”
Section: Effect Of Microtubule Dysregulation On Cf Cellular Phenotypesmentioning
confidence: 63%
See 4 more Smart Citations
“…To test this hypothesis, expression of TPPP was reduced in immortalized human tracheal 9/HTEo 2 cells. We have previously published that microtubules in CF cell tissues exhibit reduced acetylation compared with controls (16). In this article, we present data showing reduced rates of microtubule formation.…”
Section: Effect Of Microtubule Dysregulation On Cf Cellular Phenotypesmentioning
confidence: 63%
“…We have demonstrated that microtubule acetylation is reduced in CF cells and tissues (16). Reduced microtubule acetylation can be a marker of instability, and may suggest alterations in the balance of microtubule dynamics.…”
Section: Effect Of Cftr Function On Tubulin Polymerizationmentioning
confidence: 72%
See 3 more Smart Citations